Pre-Hypertension and hypertension among primary-secondary school teachers in Corum: results from a Turkish cross-sectional study - Gulay Yilmazel; Fevziye Cetinkaya (Medicine Science, 2016)
Hypertension is epidemic in worldwide nonetheless, approximately five million men and six million women are hypertensive in Turkish society. This study was aimed to determine hypertension prevalence and related factors in primary-secondary school teachers. This cross-sectional study was conducted among teachers working in pimary-secondary levels of public schools in Corum province. The study was completed by 500 teachers. A 50-item questionnaire form was generated to question socio-demographic and occupational characteristics, health-illness status, behavioral health factors and measurements of blood pressure levels of and Body Mass Index. The prevalence of hypertension was 21.4% among teachers. Blood pressure was normal in the 53.4% and was pre-hypertension level in 38.6% of participants. In hypertensives, blood pressure levels were significantly higher. According to various features such as age groups, gender, occupations of partners, years of seniority and Body mass index, blood pressure levels showed significant differences. The risk of hypertension was 2 - fold higher between the age of 35-49 and 4.5 - fold higher between the age of 50-64 than the 25-34 age groups. The risk of hypertension was 3.5 fold higher in men than in women. One of every five teachers were found to be hypertensive. This result was important to remember that teachers were a specific group of physical health problems. Ensuring appropriate primary care systems and public health services for teachers should be a priority for lifestyle changes and early medical invention in school environment. [Med-Science 2016; 5(3.000): 797-804]